Feasibility of the Italian version of the Teen Online Problem Solving Program (I-TOPS) in a sample of adolescents with acquired brain injury: Results from a randomized controlled trial - Claudia Corti; Marta Papini; Sandra Strazzer; Renato Borgatti; Romina Romaniello; Geraldina Poggi; Fabio A. Storm; Cosimo Urgesi; Ashok Jansari; Shari L. Wade; Alessandra Bardoni (PLoS ONE, 2026)
Numerous neurocognitive and behavioral deficits in adolescents with acquired brain injury have been associated with impairments in executive functions. Nevertheless, many adolescents do not receive targeted rehabilitation. One of the most validated interventions addressing executive dysfunction in this population is the web-based Teen Online Problem Solving (TOPS) program, developed in the United States in the early 2000s. This study aimed to evaluate the feasibility of the Italian version of TOPS (I-TOPS) in its first implementation in Italy, compared with an active control wellness intervention in adolescents aged 11–19 years. Data on the feasibility of both the training and the study design and procedures are reported from the randomized controlled trial conducted to assess feasibility prior to a full evaluation of efficacy. Forty-two adolescents participated, 21 allocated to I-TOPS and 21 to the wellness intervention. Overall willingness to participate in the study, assessed before randomization across the full sample, was moderate (61.73%). The I-TOPS group, but not the wellness group, demonstrated adequate training adherence, training satisfaction and participation rates. No technological issues hindering program completion, accessibility difficulties with the web-based platform or significant loss to follow-up among participants who completed the training were reported in either group. However, challenges in collecting outcome measures on parent functioning due to refusal were observed in both groups. Adherence to the planned assessment timeline was satisfactory but not fully met. In sum, the findings suggest that I-TOPS represents a feasible approach that is subjectively perceived as useful and engaging by adolescents with acquired brain injury and their families. Nevertheless, the moderate acceptance rate in the study and the potential stigma associated with reporting mental health concerns among some parents may limit the generalizability of the findings. These factors should be taken into account when planning efficacy studies. This study was registered at ClinicalTrials.gov (NCT05169788).